2018
DOI: 10.1039/c8sc01706a
|View full text |Cite
|
Sign up to set email alerts
|

Sonophore-enhanced nanoemulsions for optoacoustic imaging of cancer

Abstract: Dark Quencher, IRDye QC1 in nanoemulsion form offers excellent optoacoustic performance, suitable for non-invasive pre-clinical optoacoustic imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…The produced ultrasound waves have low attenuation in tissue, and thus allow for detection at high depths (device dependent, up to 7 cm). [ 11 ] Apart from endogenous contrast (e.g., hemoglobin, melanin), exogenous contrast agents based on noble metal nanoparticles (Au, Ag), [ 12 ] semiconducting nanoparticles, [ 13 ] synthetic melanin, [ 14 ] and small molecule dyes [ 15 ] have been explored. The latter class is particularly promising for clinical diagnostic PAI, as they can be renally cleared, pharmacokinetic properties can considerably be tuned, and they can be used as imaging tags of larger biomolecules without substantially changing their properties.…”
Section: Figurementioning
confidence: 99%
“…The produced ultrasound waves have low attenuation in tissue, and thus allow for detection at high depths (device dependent, up to 7 cm). [ 11 ] Apart from endogenous contrast (e.g., hemoglobin, melanin), exogenous contrast agents based on noble metal nanoparticles (Au, Ag), [ 12 ] semiconducting nanoparticles, [ 13 ] synthetic melanin, [ 14 ] and small molecule dyes [ 15 ] have been explored. The latter class is particularly promising for clinical diagnostic PAI, as they can be renally cleared, pharmacokinetic properties can considerably be tuned, and they can be used as imaging tags of larger biomolecules without substantially changing their properties.…”
Section: Figurementioning
confidence: 99%
“…Here, an optoacoustic agent E4x12-Cy7 was successfully synthesized, purified, chemically and optoacoustically characterized and validated in vitro and in vivo. Our rationale behind Cy7 as the absorber of choice for conjugating to neopeptide E4x12 was its high extinction coefficient and broad absorption profile 36 , ideal for optoacoustic detection. The introduction of an optoacoustic tracer, Cy7, to the 12 th position of the amino acid sequence did not perturb its binding affinity to GLP-1R, similar to what we found earlier when substituting at the 14 th position 49 .…”
Section: Discussionmentioning
confidence: 99%
“…As reported previously 4,24,26 , it can be used without significant reduction of peptide/GLP-1R target binding (~3 nM) 4 . Likewise, we have previously shown that cyanine dyes such as Cy7 exhibit the desired optical characteristics suitable for both optoacoustic and fluorescent imaging 36 . The synthesis of E4x12-Cy7 was achieved in a one-step reaction ( Figure 1B).…”
Section: Synthesis and Analysis Of E4x12-cy7mentioning
confidence: 96%
See 2 more Smart Citations